2022
DOI: 10.1002/vms3.974
|View full text |Cite
|
Sign up to set email alerts
|

HASTE MRI sequence findings correlate with loss of deep pain perception in dogs with thoracolumbar disc extrusion

Abstract: Background Thoracolumbar intervertebral disc extrusion (TL IVDE) is a common reason for the veterinary hospital admission. Various imaging factors including degree and length of compression have been tested for correlation with clinical severity, but no reliable correlation has been found. Half‐Fourier acquisition single‐shot turbo spin echo (HASTE) magnetic resonance imaging (MRI) sequences highlight the dorsal and ventral cerebrospinal fluid (CSF) columns and have been used to demonstrate spinal cord swellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(51 reference statements)
1
1
0
Order By: Relevance
“…HASTE pulse sequence was reported to be a potential prognostic tool in dogs with thoracolumbar disc extrusion and found that dogs with longitudinal extension of loss of CSF signal of <7.4 times the length of L2 were less likely to develop progressive myelomalacia (18). In our study, in dogs with cervical disc herniation, we did not observe a significant correlation between extent of loss of CSF signal on HASTE images and NS grade at presentation which corroborates findings by Khan et al in dogs with thoracolumbar disc herniation (19). Our study found a weak positive correlation with recovery time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…HASTE pulse sequence was reported to be a potential prognostic tool in dogs with thoracolumbar disc extrusion and found that dogs with longitudinal extension of loss of CSF signal of <7.4 times the length of L2 were less likely to develop progressive myelomalacia (18). In our study, in dogs with cervical disc herniation, we did not observe a significant correlation between extent of loss of CSF signal on HASTE images and NS grade at presentation which corroborates findings by Khan et al in dogs with thoracolumbar disc herniation (19). Our study found a weak positive correlation with recovery time.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, there is a paucity of studies evaluating the prognostic value of cerebral spinal fluid (CSF) attenuation length measured on HASTE pulse sequence in dogs with disc extrusion. Those studies evaluated this parameter in dogs with thoracolumbar disc extrusions (18,19). To the authors' knowledge, there is no veterinary study looking at this in dogs with cervical disc extrusion.…”
mentioning
confidence: 99%